2020
DOI: 10.1007/s11356-020-09055-x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surface modification on heavy metal adsorption performance and stability of peanut shell and its extracts of cellulose, lignin, and hemicellulose

Abstract: Effects of surface modification by carboxyl group on Pb 2+ adsorption performances and stability of peanut shell and its extracts (cellulose, lignin, and hemicellulose) were investigated. Stability of the biosorbents was measured by determining organic compound release amount (TOC). Results showed that adsorption capacity of peanut shell and the extract was poor and stability of them was not good enough. Amount of organic compound released from the unmodified sorbents followed the order: cellulose > lignin > p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(6 citation statements)
references
References 30 publications
0
6
0
Order By: Relevance
“…Moreover, metals penetrate plants mainly through the root system where most of these ions are bound to the cell wall. Therefore, the polysaccharides cellulose, lignin, and hemicellulose play an essential role in the complexation of metals [36,37]. Metal sequestration by cysteine-and glutamic acid-rich peptides such as glutathione, phytochelatins, and metallothioneins are some of the best well-known mechanisms of metal detoxification in plants.…”
Section: Elemental Analysismentioning
confidence: 99%
“…Moreover, metals penetrate plants mainly through the root system where most of these ions are bound to the cell wall. Therefore, the polysaccharides cellulose, lignin, and hemicellulose play an essential role in the complexation of metals [36,37]. Metal sequestration by cysteine-and glutamic acid-rich peptides such as glutathione, phytochelatins, and metallothioneins are some of the best well-known mechanisms of metal detoxification in plants.…”
Section: Elemental Analysismentioning
confidence: 99%
“…The interaction between NO 2 − and tertiary amines as well as secondary amines can lead to the conversion of nitrosamines in the stomach [4]. Additionally, it was indicated that NO 2 − plays a significant role in scavenging toxic and harmful substances in the human body, particularly in the stomach, thereby providing a certain level of protection to human health [25].…”
Section: Nitrite Ion Adsorption Capacity (Niac)mentioning
confidence: 99%
“…Additionally, it contains beneficial medicinal compounds such as β-sitosterol, saponin, and xylose [3]. It was reported that peanut shells (PSs) possess a significant cellulose content that holds considerable economic worth [4]. Previous studies have primarily concentrated on the utilization of the PS as a material [5,6] and biomass source [7], neglecting its potential as a valuable dietary fiber.…”
Section: Introductionmentioning
confidence: 99%
“…The calibration of the binding energy scale was done by taking the reference of the C1s peak at 284.8 eV. As shown in figure 2(b), six peaks (Pb 4f 7/2 of 136.56, 138.01, 139.35 and Pb 4f 5/2 of 141.42, 142.87, 144.25) were deconvoluted from the Pb 4f XPS band, which were ascribed to Pb, PbO, and Pb 2+ respectively [30][31][32]. For the XPS analysis results of Se, the Se 3d 5/2 peak is decomposed to three peaks at 54.78, 55.64 and 54.05 eV, corresponding to for Se and PbSe, respectively [33,34].…”
Section: Materials Characterizationmentioning
confidence: 99%